Front Cover. Issue 8 (August 2017) - Barratt, Christopher D.; Bwong, Beryl A.; Onstein, Renske E.; Rosauer, Dan F.; Menegon, Michele; Doggart, Nike; Nagel, Peter; Kissling, W. Daniel; Loader, Simon P.
Abstract : The cover image, by Christopher D. Barratt et al., is based on the Biodiversity Research Environmental correlates of phylogenetic endemism in amphibians and the conservation of refugia in the Coastal Forests of Eastern Africa, DOI:10.1111/ddi.12582 . Photo Credit: B.A. Bwong, Afrixalussylvaticus, photographed in Shimba Hills National Reserve, Kenya